THE LEGAL STATUS AND JURIDICAL IMPLICATIONS OF IKATAN NOTARIS INDONESIA AS THE EXCLUSIVE PROFESSIONAL ORGANIZATION UNDER ARTICLE 82 OF UUJN-P AND MINISTRY REGULATION NO. 24/2025 - Aisya Thalia Faz; Rahayu Subekti; Ayub Torry Satriyo Kusumo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Ikatan Notaris Indonesia (INI) has long served as the professional forum for notaries in Indonesia. Following the enactment of Law No. 2 of 2014 on Amendments to the Notary Law (UUJN-P), the organization’s status fundamentally changed from voluntary membership into a legally mandated entity, recognized as the single, exclusive professional body for notaries in Indonesia. Further regulatory reinforcement is found in Ministry Regulation No. 24/2025, which confirms INI’s position as a legal entity in the form of an association and assigns strategic authority in supervision, ethical enforcement, and professional development. This legal transformation raises critical issues regarding the hybrid nature of INI as a private legal entity endowed with public functions within the state regulatory framework for notarial office. This article analyzes the legal status of INI under Article 82 of UUJN-P, evaluates whether INI can be considered a state organ in a functional sense, and examines the juridical implications of the exclusive professional organization model on the implementation of notarial duties and public protection. Using normative juridical methods, this research concludes that while INI maintains its character as a private association, its delegated authority creates a dual position that requires clear accountability mechanisms to ensure the integrity of the notarial profession and the protection of public interest.